2010
DOI: 10.1537/ase.090513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of size and placement of developing teeth in determining anterior corpus height in prehistoric Jomon and modern Japanese mandibles

Abstract: The juvenile mandible of the modern Japanese has a lower symphysis than that of the prehistoric Jomon, while the adult symphysis is conversely higher in the modern Japanese. This cannot be explained from population differences in masticatory environments. As an alternative factor that may influence symphyseal height, we examined tooth crypt size and placement patterns in the skeletal growth series of the two populations. Results showed that although the Jomon mandible had larger bicanine breadth than in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
3
12
0
Order By: Relevance
“…Significant differences in UFH between the Jomon and the post-Jomon adolescents are apparent based on the differences in the growth trajectory between the two groups ( Figure 2B). This pattern of ontogenetic acquisition of group differences was consistent with that of nasal height, although symphyseal height showed a unique change with advancing age cohorts of relative ranking of population means (Table 2), which could be related to the difference in the spatial size for anterior teeth formation between the Jomon and Early Modern groups (Fukase and Suwa, 2010). In contrast, no significant differences in growth trajectory were found for maxillary breadth or bigonial breadth among the chronologically defined groups ( Figure 2C).…”
Section: Facial Heightsupporting
confidence: 68%
“…Significant differences in UFH between the Jomon and the post-Jomon adolescents are apparent based on the differences in the growth trajectory between the two groups ( Figure 2B). This pattern of ontogenetic acquisition of group differences was consistent with that of nasal height, although symphyseal height showed a unique change with advancing age cohorts of relative ranking of population means (Table 2), which could be related to the difference in the spatial size for anterior teeth formation between the Jomon and Early Modern groups (Fukase and Suwa, 2010). In contrast, no significant differences in growth trajectory were found for maxillary breadth or bigonial breadth among the chronologically defined groups ( Figure 2C).…”
Section: Facial Heightsupporting
confidence: 68%
“…The Jomon materials span a chronological age of approximately 5000-2350 BP, and the 'modern' Japanese are from the anatomy department collections formed at the end of the 19th/early 20th century. Further details of the samples are available in Fukase and Suwa (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Spatial requirements for housing and supporting the anterior teeth have been proposed as one potential nonmechanical factor that may determine symphyseal size and shape (e.g., Wolpoff, 1975;Wood, 1978;Chamberlain and Wood, 1985;Dean and Beynon, 1991;Taylor, 2002;Plavcan and Daegling, 2006;Coquerelle et al, 2010Coquerelle et al, , 2011Fukase and Suwa, 2010;Cobb and Panagiotopoulou, 2011;Fukase, 2011). However, the symphyseal contours of adult great apes exhibit much less variation between sexes than among species (Daegling, 1993b(Daegling, , 2001Sherwood et al, 2005;Guy et al, 2008).…”
mentioning
confidence: 99%
“…These results indicate that eventual canine size has a limited influence on intra-species symphyseal shape variation, and may refute a simple relationship between the sizes of the symphysis and teeth. However, arguments from earlier studies were mostly based on external dimensions of the adult mandible and teeth, and recent ontogenetic studies using CT data have substantially indicated that certain aspects of symphyseal configurations can develop from the spatial demands of the forming incisor and canine crypts (e.g., Coquerelle et al, 2010Coquerelle et al, , 2011Fukase and Suwa, 2010;Cobb and Panagiotopoulou, 2011;Fukase, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation